Atmospheres of digital technology: wireless spectres and ghosts outside the machine. Issue 3 (2nd July 2016) - Hernan, Luis; Dade-Robertson, Martyn
ABSTRACT: This paper examines the atmospheres of invisible technologies in the built environment. Starting with the, often cited, notion of technologies of disappearance, this paper suggest that, in the absence of physically tangible infrastructure, we understand and frame technologies through myths and historic forms of interpretation. Using the specific example of Wi-Fi networks the paper draws parallels between the operation and interpretation of modern wireless infrastructure and the spiritualism of the nineteenth century. Furthermore, it shows how through creative exploration, using a visualisation device and a photographic method developed by the authors, perceptions of these invisible infrastructures and the spaces they occupy can be played with. The work acts as an extension and critique of the way wireless infrastructure is currently described and perceived and through playful exploration may lead to new types of technology and spatial design.